2016
DOI: 10.1088/0960-1317/26/5/055013
|View full text |Cite
|
Sign up to set email alerts
|

Efficient capture of magnetic microbeads by sequentially switched electroosmotic flow—an experimental study

Abstract: Magnetophoretic separation is a commonly used immunoassay technique in microfluidic platforms where magnetic microbeads (mMBs) coated with specific epitopes (antibodies) entrap target pathogens by antigen-antibody kinetics. The mMB-cell complexes are then separated from the continuous flow using an external magnetic field. The goal of this study was to design and test a microfluidic device for efficient separation of fluorescence-tagged mMBs driven by electroosmotic flow (EOF) under steady (time invariant) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…This study provides improved analysis of the capture efficiency of the device designed previously by our group and published in Das et al [20]. It is important to efficiently capture the mMBs in order to produce accurate and reliable results with the greatest sensitivity possible.…”
Section: Proposed Designmentioning
confidence: 96%
See 4 more Smart Citations
“…This study provides improved analysis of the capture efficiency of the device designed previously by our group and published in Das et al [20]. It is important to efficiently capture the mMBs in order to produce accurate and reliable results with the greatest sensitivity possible.…”
Section: Proposed Designmentioning
confidence: 96%
“…The previous studies have shown how multiple passes can increase capture of mMBs using the implementation of a switching protocol to return initially uncaptured mMBs to the device [5,20]. It was hypothesized that the switching protocol integrated into this device will return the mMBs to the area of higher magnetic field, allowing for more mMBs to be captured, and thus increasing the capture efficiency.…”
Section: Proposed Designmentioning
confidence: 99%
See 3 more Smart Citations